Demagnetization fault detection by a novel and flexible modeling method for outer rotor permanent magnet synchronous machine. (March 2020) - Sharouni, Sahar; Naderi, Peyman; Hedayati, Mahdi; Hajihosseini, Payman
Highlights: An original Magnetic Equivalent Circuit (MEC) method is presented for Outer Rotor Permanent Magnet Synchronous Machine for first time. The model accuracy can be tuned by some selectable parameters in the model. Demagnetization fault diagnosis method is presented for first time for the above-mentioned machine. Saturation effect is modeled by a novel method, therefore all of the space and time harmonics are considered in the presented model. Very shorter processing time during is obtained compared to FEM. Therefore, the presented method is a suitable choice for electric machines modeling. Abstract: The research presents a novel technique for modeling of Outer Rotor Permanent Magnet Synchronous Machines (OR-PMSMs) in healthy and faulty cases with demagnetization fault based on an improved Magnetic Equivalent Circuit (MEC) method. Saturation effect is considered by a new method, where the B-H curve fitting is performed by using a novel nonlinear function. The machine properties such as the number of poles, number of slots, magnets size and all of the other parameters can be selected arbitrarily in the proposed model. Noticing to machine structure, the machine geometry is divided into 11 individual zones. Each of the flux tubes in the core is modeled by a nonlinear reluctance and the machine performances in both transient and steady-state conditions are studied. Various machine properties such as magnets arc, winding configuration, and slot skewing angle are analyzed and the dynamic behaviour is compared in various cases. Comparison with Finite-Element-Method (FEM) shows the effectiveness and accuracy of the proposed MEC method and much shorter processing time compared to FEM.